A Temporal Analysis of Female Work Participation Rate in India and Haryana: 1971 to 2011: Trends and Patterns in Female Work Participation in India and Haryana (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The present study is a comparative analysis of female work participation rate in India and Haryana. The study is temporal in nature it is studied from 1971 to 2011. Women consist about 50 percent of country’s population and they play a very significant role in the development of a country. The female work participation has been studied for both total (crude) and adult population. Work participation is defined as a worker taking part in any economic activity. Work is measured with the help of work participation rate. The study is based on secondary data taken from census of India for various years. The study concluded that over time female work participation rate has been increased in both India and Haryana.